Interaction between protokimberlite melts and mantle lithosphere: Evidence from mantle xenoliths from the Dalnyaya kimberlite pipe, Yakutia (Russia) - I.V. Ashchepkov (Institute of Geology and Mineralogy, SD RAS); T. Ntaflos (University of Vienna); Z.V. Spetsius (Alrosa Stock Company); R.F. Salikhov (Alrosa Stock Company); H. Downes (Department of Earth and Planetary Sciences, Birkbeck University of London) (Geoscience Frontiers, 2017)
The abstract is available here: https://uscholar.univie.ac.at/o:869187 The abstract is available here: https://uscholar.univie.ac.at/o:869187